Challenges and Activities of Professional Librarians’ Associations, Particularly for Association of Hungarian Librarians before and during COVID aera - Hajdu Barat, Ágnes (Access: An International Journal of Nepal Library Association, 2022)
This paper studies the influence of the international and national trends, changings, and challenges to professional librarians’ associations. It summarizes basic endeavours of management and summarizing permanent updated visions of Association of Hungarian Librarians (AHL). I try to collect different aspects from the specific and general viewpoints. In this study we would like to introduce some national and international initiatives, including possibilities for mutual cooperation. We will introduce the vision of AHL, focus on up-to-date knowledge and adequate competencies before and during COVID aera.